Meta Analysis and Verification on Automated Image Tagging Techniques - Khoria, S (International Journal of Computer Sciences and Engineering, 2019)
Automatic image tagging is an active topic of research in computer vision and pattern recognition. There is a huge urge in the Computer Vision community today to find ways to automatically annotate images. Machine learning techniques have facilitated image retrieval by automatically classifying and annotating images with keywords. Among them Support Vector Machines (SVMs) have been used extensively due to their generalization properties.